Effect of NPK, Humic Acid, Biofertilizer and Light Intensity on Vegetative Growth and Bulb Production of Narcissus trilandrus L. and Hyacinthus orientalis L. - Sazar S. Noraldeen; Sabiha S. Mustafa; Asmaa S. Ahmed (Zanco Journal of Pure and Applied Sciences, 2023)
This research was carried out in order to compare among three different fertilizers: bio, chemical, and organic. on two plants selected to conduct this research were (Narcissus and Hyacinths), which were cultivated in shaded and non-shaded locations from Autumn 2020 to Spring 2021 in Gerdarash field at the college campus. The vegetative traits of the two plants, as well as the production of bulblets, were measured properly. Regarding Narcissus, the bio-fertilizer showed the most promising result when it came to the number of leaves and bulblets (3.67, 1.67 per plant respectively). The chemical fertilizer showed better results in the height of the plants (32.67 cm) and the diameter of the flowers (11 cm). The organic fertilizer was compared to the control. For the Hyacinth plants, the bio-fertilizer proved its superiority in plant height (27 cm), flower petiole length (12.33 cm), number of flowers (32.33), flower diameter (6.33cm), and new bulblets with three ones compared to another treatment and control. Whereas for lighting, we recommend planting the ornamental bulbs in open and non-shaded places as it obtained the best results for vegetative and floral traits for both plants.